2021
DOI: 10.3390/ijms22052766
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression-Related Changes in Morphologies of Organelles and Cellular Component Organization in Mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPS) are inherited metabolic diseases characterized by accumulation of incompletely degraded glycosaminoglycans (GAGs) in lysosomes. Although primary causes of these diseases are mutations in genes coding for enzymes involved in lysosomal GAG degradation, it was demonstrated that storage of these complex carbohydrates provokes a cascade of secondary and tertiary changes affecting cellular functions. Potentially, this might lead to appearance of cellular disorders which could not be corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…After translation, GALNS undergoes post-translational modification in the endoplasmic reticulum (ER)-Golgi apparatus (GA) pathway to attach mannose motifs in the Asn204/Asn423 residues and phosphorylate them, respectively 58 , which are crucial for sorting of lysosomal proteins 59 , 60 . In this regard, structural analysis of intracellular organelles of MPS IVA fibroblasts has revealed changes in the number, length, and width on the GA but not on the ER 61 . Consequently, we hypothesized a partially impaired processing of the overexpressing GALNS enzyme in the GA after Donor AAVS1:GALNS insertion in the AAVS1 locus.…”
Section: Discussionmentioning
confidence: 98%
“…After translation, GALNS undergoes post-translational modification in the endoplasmic reticulum (ER)-Golgi apparatus (GA) pathway to attach mannose motifs in the Asn204/Asn423 residues and phosphorylate them, respectively 58 , which are crucial for sorting of lysosomal proteins 59 , 60 . In this regard, structural analysis of intracellular organelles of MPS IVA fibroblasts has revealed changes in the number, length, and width on the GA but not on the ER 61 . Consequently, we hypothesized a partially impaired processing of the overexpressing GALNS enzyme in the GA after Donor AAVS1:GALNS insertion in the AAVS1 locus.…”
Section: Discussionmentioning
confidence: 98%
“…Sanfilippo syndrome revealed the highest dysregulation of gene expression among MPS diseases, with numbers of down-and up-regulated transcripts (relative to healthy cells) exceeding 700 in every MPS III subtype. 32 Such global changes in levels of transcripts and proteins encoded by them result in dysmorphology and dysfunctions of different cellular organelles (like nucleus, mitochondria, endoplasmic reticulum, Golgi apparatus), 33 as well as abnormalities in various cellular processes. 34 Among them, apoptosis, 35 cell activation, 36 proteasomal degradation, 37 homeostasis of different ions (especially Ca 2+ , Fe 2+ and Zn 2+ ), 38 signal transduction, 39 and cell cycle, 40 are especially strongly affected.…”
Section: Complexity Of Sanfilippo Disease Pathomechanismsmentioning
confidence: 99%
“…42 Furthermore, some of these changes in gene expression regulation could not be reversed after effective decreasing levels of stored GAGs, suggesting that these dysfunctions are either irreversible or require additional manipulations (along with abolition of the storage) to be corrected. 42 Indeed, it was demonstrated experimentally that some cellular abnormalities could not be corrected by reduction of GAG storage; these included changes in organelles, 33 and proteasomal functions. 37 Very recent investigations demonstrated that some proteins involved in the signal transduction-mediated control of gene expression, like GPER1 and OXTR receptors, form aggregates which arise as effects of their interactions with undegraded GAGs.…”
Section: Complexity Of Sanfilippo Disease Pathomechanismsmentioning
confidence: 99%
“…One of the major challenges in developing effective treatment for MPS is the fact that some severe symptoms arise from lesions of hard-to-reach tissues and organs, such as the central nervous system or the skeleton. On the other hand, the existence of additional mechanisms of MPS pathogenesis, in addition to GAG storage, which are poorly understood, has been suggested and demonstrated experimentally [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Describing such mechanisms could indicate not only new mechanisms of the pathogenesis of this rare disease, but also the direction to develop effective therapies in the future.…”
Section: Introductionmentioning
confidence: 99%